Development of Single Variable Linear Equation System Question Instruments Based on Higher Order Thinking Skill (HOTS) - Hidayatul Maratin; Ali Shodikin (Pedagogi: Jurnal Ilmu Pendidikan, 2022)
The 2013 curriculum requires learners to be able to think of high levels or HOTS that suit the needs of competence in the 21st century. Based on the results of the study stated if, the ranking of learners in Indonesia is still relatively low because learners are still weak in solving problems that require reasoning and analysis. So it can be concluded that the purpose of this research is to develop HOTS-based SPLSV problems in SMP / MTs that are valid, practical, and effective. This research is a research development (research and development). The test subjects in this study were class VII students at MTS I Attanwir, with a population of 40 students, and to focus the data, selected 3 students who represented from high, medium, and low abilities. The analysis used in this study is a test of validity by expert material, validity of the problem, differentiating power, difficulty level, rehabilitation test, and t-test testing. The results of the study suggest that a set of SPLSV problem instruments can be used to train high-level thinking skills in learners.